2015
DOI: 10.1021/acsnano.5b01354
|View full text |Cite
|
Sign up to set email alerts
|

Exciton Fine Structure of CdSe/CdS Nanocrystals Determined by Polarization Microscopy at Room Temperature

Abstract: We present a method that allows determining the band-edge exciton fine structure of CdSe/CdS dot-in-rods samples based on single particle polarization measurements at room temperature. We model the measured emission polarization of such single particles considering the fine structure properties, the dielectric effect induced by the anisotropic shell, and the measurement configuration. We use this method to characterize the band-edge exciton fine structure splitting of various samples of dot-in-rods. We show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 44 publications
(138 reference statements)
4
89
2
Order By: Relevance
“…These studies have found dipolar nature (1D or 2D) to be related both to the symmetry and degeneracy of the electron-hole transition dipole, and also to the shape of the nano-object, even when the Bohr radius of the exciton is smaller than the size of the nanoobject, a size difference that should made the dipolar transition insensitive to spatial confinement. A relationship between shape and polarized radiation has been shown, in particular, for colloidal dot-in-rods, and has sometimes been interpreted as a dielectric antenna effect of the rod-like shell [7,[9][10][11][12]. This has also been observed for nanowires [13] and porous silicon [14].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…These studies have found dipolar nature (1D or 2D) to be related both to the symmetry and degeneracy of the electron-hole transition dipole, and also to the shape of the nano-object, even when the Bohr radius of the exciton is smaller than the size of the nanoobject, a size difference that should made the dipolar transition insensitive to spatial confinement. A relationship between shape and polarized radiation has been shown, in particular, for colloidal dot-in-rods, and has sometimes been interpreted as a dielectric antenna effect of the rod-like shell [7,[9][10][11][12]. This has also been observed for nanowires [13] and porous silicon [14].…”
Section: Introductionmentioning
confidence: 89%
“…In both cases, polarized emission can be observed, with the degree of polarization depending of their orientation (with polarization degree higher for 1D dipoles). Analyses using polarimetric methods, sometimes combined with defocused imaging or decay curves, have demonstrated 2D-dipole behavior for spherical core-shell quantum dots [1][2][3][4] and dot-in-plate structures [5], and 1D-dipole behavior for nanorods [6] and dot-in-rods [7], with intermediate 1D+2D behavior for some structures [8,9]. These studies have found dipolar nature (1D or 2D) to be related both to the symmetry and degeneracy of the electron-hole transition dipole, and also to the shape of the nano-object, even when the Bohr radius of the exciton is smaller than the size of the nanoobject, a size difference that should made the dipolar transition insensitive to spatial confinement.…”
Section: Introductionmentioning
confidence: 99%
“…These emitters, although featuring a certain amount of blinking [22] and bleaching [23], and a non-negligible probability of two-photon emission, are very convenient due to their room-temperature operation and relatively simple production. The 'dot-in-rod' (DR) modification [24] is especially promising because of reduced blinking and a high degree of polarization [25][26][27]. Clusters are easily formed [8,28] by dropping a DR solution onto a substrate and leaving the solvent to evaporate, the mean number of DRs in a cluster depending on the solution concentration.…”
Section: Methodsmentioning
confidence: 99%
“…In our experimental setup, we study light from clusters of single-photon emitters which we detect with the help of time-bin multiplexed click detection. We used multiphoton light emitted by clusters of colloidal CdSe/CdS quantum "dot in rods" (DRs) [49][50][51][52] coated on a fused ) is focused into a cluster of DRs through objective lens O1 and then cut off by the filters F. The radiation emitted by the cluster is coupled into an objective lens O2 and, after filtering, is sent into the fiber-assisted multiplexed detection setup where two detectors D1, D2 and two different path lengths create four detection channels, C1, . .…”
Section: Methodsmentioning
confidence: 99%